Examining the sustainability and development challenge in agricultural-forest frontiers of the Amazon Basin through the eyes of locals - Blanco Gutiérrez, I.; Manners, Rhys; Varela Ortega, C.; Tarquis, A.; Martorano, L.G.; Toledo, M. (Copernicus GmbH, 2020)
The Amazon basin is the world’s largest rainforest and the most biologically diverse place on Earth. Despite the critical importance of this region, Amazon forests continue inexorably to be degraded and deforested for various reasons, mainly a consequence of agricultural expansion. The development of novel policy strategies that provide balanced solutions, associating economic growth and environmental protection, is still challenging, largely because the perspective of those most affected- local stakeholders- is often ignored. Participatory Fuzzy Cognitive Mapping (FCM) was implemented to examinestakeholder perceptions towards the sustainable development of two agricultural-forest frontier areas in the Bolivian and Brazilian Amazon. A series of development scenarios and a climate change scenario were explored and applied to stakeholder derived FCM. Stakeholders in both regions perceived landscapes of socio-economic impoverishment and environmental degradation driven by governmental and institutional deficiencies. Under such abject conditions, governance and well-integrated social and technological strategies offered socio-economic development, environmental conservation, and resilience to climatic changes. The results suggest the benefits of a new type of thinking for development strategies in the Amazon basin, and that continued application of traditional development policies reduce the resilience of the Amazon to climate change, whilst limiting socio-economic development and environmental conservation.